2019
DOI: 10.1097/01.ogx.0000553115.73937.07
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembly of Embryonic and Two Extraembryonic Stem Cell Types Into Gastrulating Embryo-like Structures

Abstract: Embryonic stem (ES) cells can be incorporated into the developing embryo and its germ line but when cultured alone, their ability to generate embryonic structures is restricted. They can interact with trophoblast stem (TS) cells to generate structures that break symmetry and specify mesoderm, but their development is limited as the epithelial-mesenchymal-transition (EMT) of gastrulation cannot occur. Here we describe a system that, for the first time, allows assembly of mouse ES, TS and extraembryonic-endoderm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 24 publications
(31 reference statements)
0
11
0
Order By: Relevance
“…Particularly when considered in conjunction with data from systems that employ extra-embryonic cell types or mimic associated cues, for instance ETS, (i)ETX embryos and blastoids [65,66,67,68], the characterization of such a basal developmental mode as performed in this study can provide deeper insight into fundamental principles of early patterning by helping to delineate which aspects of mammalian body plan establishment are inherent to ESCs and which ones strictly require embryo-like geometry as well as external biochemical and mechanical signals.…”
Section: An Alternative Developmental Mode?mentioning
confidence: 99%
“…Particularly when considered in conjunction with data from systems that employ extra-embryonic cell types or mimic associated cues, for instance ETS, (i)ETX embryos and blastoids [65,66,67,68], the characterization of such a basal developmental mode as performed in this study can provide deeper insight into fundamental principles of early patterning by helping to delineate which aspects of mammalian body plan establishment are inherent to ESCs and which ones strictly require embryo-like geometry as well as external biochemical and mechanical signals.…”
Section: An Alternative Developmental Mode?mentioning
confidence: 99%
“…The embryo model that was improved with genetic engineering is called ETX, a model that partially recapitulates mouse development by combining embryonic stem cells (ESCs), trophoblast stem cells (TS), and extra-embryonic endoderm (XEN) stem cells (Sozen et al, 2018). It was shown that ETX embryos are transcriptionally similar to the mouse embryo at around gastrulation stage, but they were unable to recapitulate all the complex morphogenetic events that characterize murine gastrulation.…”
Section: Perspectivementioning
confidence: 99%
“…Mouse EPS embryos (mEPSCs+mTSCs) [24] Inverted pyramidal microwells (AggreWell) [24] -EPS blastoids develop better cystic structures in hypoxic conditions of 5% O2 compared to normal conditions [24] -PaE-like cells distributed along the TE migrating from PrE resembled an E4.5 embryo [24] -The PaE-like cells were validated by the group of cells expressing Snail, Follistatin, Vimentin, Grem2, and Stra6 on single-cell transcriptomics data [24] E3.5-E5.0 ETX embryo (ES+TS+XEN) [28,35] Inverted pyramidal microwells (AggreWell) Single-cell suspensions of 3 cell types seeded together [28] Non-adherent suspension shaking culture [35] -Self-organization of XEN cells along with ES and TS cells, fulfilled the requirement for spontaneously inducing an anterior symmetry breaking event with AVE specification and epithelial-mesenchymal transition (EMT) [28] E5.25-E7.0…”
Section: Mouse Ets Embryo (Mescs+mtscs)mentioning
confidence: 99%
“…In another approach, mouse post-implantation models that mimic gastrulation [14,28,36,39] could be explored further for the formation of ExEm tissues or precursors after the formation of the PS. Currently, these systems are not co-regulated by the formation of ExEm tissues due to the absence of these cell types to begin with, for instance in gastruloids, or the potential to form ExEm tissues is lost through the specific signals they are exposed to.…”
Section: Formation Of the Extra-embryonic Placenta In Vitromentioning
confidence: 99%
See 1 more Smart Citation